Economic Analysis of Beef Cattle Production Under Extensive and Semi-Intensive Management Systems in Sorong Regency, Southwest Papua - Rahmawati, Afika Dwikesuma; Prasetia, Muh Andika; Anggriani, Rini; Lena, Mirza; Two Sulfiar, Ahmat Endang (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The length the research aims to determine the livestock profile and explore sustainable production income on beef cattle farms with different rearing systems in Sorong Regency. Data collection uses the Participatory Rural Appraisal method, which is an approach that involves family members or.Individuals to analyze the reality of the living conditions they live in. This research involved 90 breeders who were selected using purposive sampling based on 4 considerations. The analysis used to test the differences in different maintenance systems is the independent T-test analysis. The research results show that the number of cows in the extensive system was higher than in the semi-intensive system (P<0.05). The same thing applies to net body weight production, production economics, the economics of the function of livestock as savings and insurance, extensive breeders are higher than semi-intensive breeders (P<0.05). The total income/benefit of intensive breeders is higher than extensive breeders IDR. 42,423 ± 26,162 million vs. IDR. 19,952 ± 11,116 million. Based on the research results, it can be concluded that the extensive livestock system produces high income and has the potential to maintain their livestock in a sustainable manner than the semi-intensive system.